1990
DOI: 10.1002/bies.950121108
|View full text |Cite
|
Sign up to set email alerts
|

Problems And Paradigms: Ionising radiations from nuclear establishments and childhood leukaemias – an enigma

Abstract: The Gardner report, recently published in the UK, showing a correlation between incidence of childhood leukaemia and paternal exposure to ionising radiations (amongst fathers working in nuclear power plants) has added a new element to debates about both the risk factors in nuclear power plants and the relationships between ionising radiations and leukaemogenesis. The epidemiologic and genetic evidence concerning leukaemias is reviewed here and it is concluded that the leukaemogenic agent, whose existence is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…This preconceptional irradiation (PPI) hypothesis suggested a new mechanism of leukaemogenesis in humans, and was highly controversial, as there was little evidence from other sources to suggest that childhood leukaemia could be caused by germline mutation. Moreover, fathers' radiation exposure was considered to be insufficient to cause the mutation rate required for the number of cases observed (Evans, 1990;Doll et al, 1994;Wakeford et al, 1994). Additionally, there was no evidence of a germline effect among the children of Japanese atomic bomb survivors (Kodaira et al, 1995(Kodaira et al, , 2004Izumi et al, 2003).…”
mentioning
confidence: 99%
“…This preconceptional irradiation (PPI) hypothesis suggested a new mechanism of leukaemogenesis in humans, and was highly controversial, as there was little evidence from other sources to suggest that childhood leukaemia could be caused by germline mutation. Moreover, fathers' radiation exposure was considered to be insufficient to cause the mutation rate required for the number of cases observed (Evans, 1990;Doll et al, 1994;Wakeford et al, 1994). Additionally, there was no evidence of a germline effect among the children of Japanese atomic bomb survivors (Kodaira et al, 1995(Kodaira et al, , 2004Izumi et al, 2003).…”
mentioning
confidence: 99%
“…As a consequence, the report in 1990 by colleagues (1990a, 1990b) of the initial results of the West Cumbria leukaemia and lymphoma case-control study, showing statistically significant associations between leukaemia, or leukaemia and non-Hodgkin's lymphoma (NHL), in young persons (under 25 years of age) and doses of radiation recorded by film badges worn by fathers employed at the Sellafield nuclear installation before the conception of their children, generated considerable debate within the scientific community. The possibility of there being a causal connection between paternal preconception irradiation (PPI) and leukaemia in offspring, of the magnitude suggested by this study, was met with some scepticism (Abrahamson 1990, Evans 1990, Narod 1990, Baverstock 1991, Neel 1991, Sankaranarayanan 1992. Suggestions were made (Beral 1990, Gardner et al 1990b that the discrepancy between the leukaemia PPI risks in the West Cumbria study and those observed in the main human F 1 (first generation offspring) dataset (Yoshimoto et al 1990) might be related to the presence of internally deposited radionuclides in the Sellafield workforce, and in particular the alpha-particle emitting radioisotopes of plutonium, the organ doses from which were not taken into account in the West Cumbria study (Gardner et al 1990b).…”
Section: Introductionmentioning
confidence: 81%
“…The findings remain controversial [Beral, 1990;Evans, 1990;MacMahon, 1992;Doll et al, 19941. The results have been questioned on several grounds, including lack of consistency with the Japanese atomic bomb results, other studies of cancer in children of nuclear plant workers that did not find any association, the lack of an increase in genetic diseases or birth defects in the Sellafield area, or the contention that the association was due to other exposures such as viruses.…”
Section: Atomic Bomb Survivorsmentioning
confidence: 99%